Cyclic Voltammetry and Spectrophotometric Determination of Antioxidant Activities of Selected Ginger Species - Barbosa, Gina Batoy; Gomez, Enjelyn; Inutan, Ellen D. (Asian Journal of Biological and Life Sciences, 2018)
Introduction:Zingiberaceaerhizomes are commonly investigated due to its applications in food and traditional medicine use. However, less scientific attention was given to its leaves.Aim:This study primarily aimed to compare the antioxidant activity of the leaves and rhizomes of commonZingiberaceaeplants namely:Zingiber officinale, Curcuma longaandEtlingera elatior.Methods:Antioxidant activity of the water and ethanol extracts of the leaves and rhizomes of the studied plants was determined using cyclic voltammetry (CV) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) assays.Results:Very low positive correlation (r = 0.22) of antioxidant activities was observed between DPPH and CV methods. In both DPPH and CV methods,E. elatiorhas generally higher antioxidant activity in leaves than in rhizomes and water extract than ethanol extracts. Higher antioxidant activity was observed in leaves than in rhizomes forZ. officinaleandC. longafor both water and ethanol extracts. In general, water extracts of the three ginger plants have higher antioxidant activity than its ethanol extracts.Conclusion:Both CV and DPPH assay revealed that leaves of common gingers studied are potential sources of antioxidants.
Keywords: Cyclic voltammetry; DPPH radical scavenging activity; Gingers